THE APPLICATION OF STAD COOPERATIVE LEARNING IN IMPROVING MATHEMATICS LEARNING ABOUT FRACTIONS AT THE FIFTH GRADE STUDENTS OF SDN KURIPAN 02 IN ACADEMIC YEAR 2013/2014. - KHAYATI, IKA NUR (KALAM CENDEKIA PGSD KEBUMEN, 2018)
The application of STAD Cooperatif Learning in improving Matematics about Fractions at the fifth grade students of SDN Kuripan 02 in Academic Year 2013/2014. The purpose of this research is to improve mathematics learning about fractions in fifth grade elementary school. Is a research subject Elementary School fifth grade students Kuripan 02 school year 2013/2014, amounting to 34 students. Source data from this study were students, fifth grade teacher and peers. Validity using triangulation of data collection techniques and data sources. Analysis of the data used is the analysis of quantitative data and qualitative data analysis. This research is Classroom Action Research (CAR), which is carried out in three (3) cycles consisting of planning, implementation, observation, and reflection. The results showed that the application of STAD Cooperative learning  can improve learning fractions in math.